2020
DOI: 10.11121/ijocta.01.2020.00753
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of fractional integro-differential systems based on a spectral method and grey wolf optimizer

Abstract: This paper elaborated an effective and robust metaheuristic algorithm with acceptable performance based on solution accuracy. The algorithm applied in solution of the optimal control of fractional Volterra integro-differential (FVID) equation which be substituted by nonlinear programming (NLP). Subsequently the FIVD convert the problem to a NLP by using spectral collocation techniques and thereafter we execute the grey wolf optimizer (GWO) to improve the speed and accuracy and find the solutions of the optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…At the end, a comparison between the obtained optimal performance indicator J with the suggested method and the other ones reported in Khanduzi et al (2020) for N = 7, where α = 1 and M = N + 2 is reported in Table 4 (for Examples 1, 2 and 3). As can be seen, the superiority of the method for solving NVIFs is clear that the implementation of Chelyshkov polynomials is efficient and accurate.…”
Section: Selected Numerical Examples and Comparisonsmentioning
confidence: 99%
“…At the end, a comparison between the obtained optimal performance indicator J with the suggested method and the other ones reported in Khanduzi et al (2020) for N = 7, where α = 1 and M = N + 2 is reported in Table 4 (for Examples 1, 2 and 3). As can be seen, the superiority of the method for solving NVIFs is clear that the implementation of Chelyshkov polynomials is efficient and accurate.…”
Section: Selected Numerical Examples and Comparisonsmentioning
confidence: 99%
“…Moreover, some numerical schemes are proposed for solving OCPs by integer and non-integer integro-differential equations such as the methods based on fractional-order Legendre functions (Rabiei et al (2018)), discrete Hahn polynomials (Mohammadi et al (2022)), Orthonormal piecewise Bernoulli functions (Heydari et al (2022)), hybrid of block-pulse functions and Legendre polynomials (Marzban (2020)), spectral method and grey wolf optimizer (Khanduzi et al (2020)), Chebyshev approximations (El-Kady and Moussa (2013)), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing results concern the existence of a solution to (), its uniqueness and continuous dependence on parameters, as well as numerical methods of finding it. Numerical solutions to optimal control problems governed by integro‐differential equations of Volterra type were studied, for example, in Reference 2 (case of nonlinear control system and nonlinear integral cost functional), and in References 3 and 4 (case of linear system and quadratic cost functional). Optimal control of feedback type involving also the past history of the solution has been obtained in Reference 5 for a scalar linear system (with f 2 = u ) and quadratic cost functional.…”
Section: Introductionmentioning
confidence: 99%